2014
DOI: 10.1038/modpathol.2013.251
|View full text |Cite
|
Sign up to set email alerts
|

High EGFR gene copy number predicts poor outcome in triple-negative breast cancer

Abstract: Epidermal growth factor receptor (EGFR) is frequently overexpressed in triple-negative breast cancer and is emerging as a therapeutic target. EGFR gene copy number alteration and mutation are highly variable and scientists have been challenged to define their prognostic significance in triple-negative breast cancer. We examined EGFR protein expression, EGFR gene copy number alteration and mutation of exon 18 to 21 in 151 cases of triple-negative breast cancer and correlated these findings with clinical outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
171
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(181 citation statements)
references
References 35 publications
6
171
2
2
Order By: Relevance
“…EGFR overexpression is mostly due to EGFR gene amplification or mutations, with the latter occurring frequently in EGFR exons 18-21, which encode the tyrosine kinase section of the EGFR protein. Previous studies have demonstrated an association between EGFR alterations and aggressive biological behaviors (e.g., tumor cell dedifferentiation, advanced tumor stage or cancer metastasis) of different human cancers of epithelial origin, including head and neck, breast, colon, stomach and lung cancer (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (20)(21)(22). EGFR amplification and protein overexpression have been reported in ESCC and premalignant lesions (3,9,19) and the overexpression of EGFR was found to be significantly associated with the depth of invasion of the tumor (9).…”
Section: Introductionmentioning
confidence: 99%
“…EGFR overexpression is mostly due to EGFR gene amplification or mutations, with the latter occurring frequently in EGFR exons 18-21, which encode the tyrosine kinase section of the EGFR protein. Previous studies have demonstrated an association between EGFR alterations and aggressive biological behaviors (e.g., tumor cell dedifferentiation, advanced tumor stage or cancer metastasis) of different human cancers of epithelial origin, including head and neck, breast, colon, stomach and lung cancer (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (20)(21)(22). EGFR amplification and protein overexpression have been reported in ESCC and premalignant lesions (3,9,19) and the overexpression of EGFR was found to be significantly associated with the depth of invasion of the tumor (9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, its overexpression is ra-Advances in Breast Cancer Research lated with the poor disease-free survival of TNBC [14]. Moreover, recent studies have shown that cetuximab as a EGFR target drug can increase the total remission rate of TNBC [15].…”
Section: Discussionmentioning
confidence: 99%
“…The eleven lines tested included triple negative and Her2 positive breast cancers of grade 2 or higher, and we observed that Llgl1 loss was associated with increased EGFR expression. EGFR expression, high CD44 expression, and migration have all been linked to decreased patient survival [39][40][41][42][43][44]. We therefore analyzed a publicly available GEO data set (GSE3494) with 236 breast cancer patients for Llgl1 expression and long term survival ( Figure 7E).…”
Section: Llgl1 Expression Correlates With Prolonged Survival In Metasmentioning
confidence: 99%